THE INFLUENCE OF POLYACRYLAMIDE (PAA) ON HYDROGEN EVOLUTION REACTION AT THE POLYCRYSTALLINE GOLD - D. Ĉamovska; M. Cvetkovska; T. Grčev (Journal of Engineering & Processing Management, 2010)
The influence of polyacrylamide (PAA; Mn between 5∙103 and 1.5∙106 gmol-1) on hydrogen evolution reaction at the polycrystalline gold in 0.5 M H2SO4 was studied using potentiodynamic measurements (5 mV/s) in the potential range from 0 to -0.6 V/she. It was concluded that formation of protective layer of PAA, adsorbed on the electrode surface, is responsible for inhibition of hydrogen evolution reaction. The further investigations, especially on iron and steel in acid solutions (real corrosion system) confirm the effective inhibition of corrosion by PAA.
Keywords: polyacrylamide; hydrogen evolution reaction; polycrystalline gold